Mensuration of the rabbit pituitary gland from computed tomography. Issue 3 (13th March 2020) - Kwan, Vionna; Quesenberry, Katherine; Le Roux, Alexandre B.
Abstract: The aim of this retrospective reference interval observational study was to determine the mensuration of the pituitary gland (hypophysis cerebri) by analyzing CT studies in rabbits without clinical evidence of pituitary disease or central neurologic signs. Though diseases of the rabbit pituitary gland are uncommon, the pituitary gland is essential in regulation of the rabbit's endocrine system, as in other species. Currently, there are minimal published studies that detail the rabbit head anatomy on cross‐sectional imaging, and even less specifically examining the pituitary gland. The pituitary gland was measured by one observer at a single time point from transverse and reconstructed sagittal CT images in a soft‐tissue algorithm in 62 rabbits for a total of 66 rabbit head CT studies. The rabbits ranged from 0.84 to 14 years in age (mean ± SD: 5.46 ± 3.05 years) and 0.92 to 4.95 kg in weight (2.21 ± 0.83 kg). Linear pituitary measurements were performed using electronic calipers. The mean ± SD pituitary height was 4.22 ± 0.57 mm, width was 4.48 ± 0.71 mm, and length was 6.02 ± 0.70 mm. The pituitary gland height‐to‐brain area ratio was 1.10 ± 0.16 mm −1, which is much higher than the values reported in normal dogs and cats. The age, weight, and sex of the rabbits were not found to have a significant impact on pituitary gland mensuration. These measurements could be useful as a reference range for future rabbit head CT studies and to rule out pituitary enlargement or disease when evaluating rabbit pituitary glands.